2014
DOI: 10.3386/w20181
|View full text |Cite
|
Sign up to set email alerts
|

Dominated Choices and Medicare Advantage Enrollment

Abstract: Research in behavioral economics suggests that certain circumstances, such as large numbers of complex options or revisiting prior choices, can lead to decision errors. This paper explores the enrollment decisions of Medicare beneficiaries in the Medicare Advantage (MA) program. During the time period we study (2007)(2008)(2009)(2010), private fee-for-service (PFFS) plans offered enhanced benefits beyond those of traditional Medicare (TM) without any restrictions on physician networks, making TM a dominated ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Afendulis et al, who compared the enrollment decisions of Medicare beneficiaries in the United States, found that the longer an individual had been enrolled in an inferior program, the less likely the individual was to switch to a newly offered superior program. 12 In our study, individuals had not been allowed to switch their health insurance before 1996. Hence, age can be seen as a proxy for the length of enrollment and the age effect might be at least partially explained by that.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Afendulis et al, who compared the enrollment decisions of Medicare beneficiaries in the United States, found that the longer an individual had been enrolled in an inferior program, the less likely the individual was to switch to a newly offered superior program. 12 In our study, individuals had not been allowed to switch their health insurance before 1996. Hence, age can be seen as a proxy for the length of enrollment and the age effect might be at least partially explained by that.…”
Section: Discussionmentioning
confidence: 99%
“…decisions regarding health insurance plans. 12,13 Large-scale studies often exploit natural experiments, e.g. when at some point in life individuals are offered to switch to a new superior health care plan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study increases knowledge of how patients' clinician choices are influenced by the level of aggregation and presentation of healthcare quality data. Some questions about roll-up scores remain unaddressed, including how clinicians or health plans respond to roll-up measures or use them to guide quality improvement initiatives 32,33 and determining best methods of roll-up score calculation.…”
Section: Discussionmentioning
confidence: 99%
“…A significant example is status quo bias in the Medicare market, which causes some individuals who enrol in MA to remain in the programme over long periods of time. Indeed, only a tiny fraction of enrolees in TM switch into MA (Sinaiko et al , 2013; Afendulis et al , 2014). McWilliams et al (2011) find evidence consistent with ‘choice overload’, showing that rates of enrolment in MA increased as plan choices increased up to 15, then plateaued with 16–30 plan choices and then declined when beneficiaries had more than 30 choices available.…”
Section: Study Context Data and Methodsmentioning
confidence: 99%